Observation of surgical stabilization of LII uncomplicated burst fracture and LIV compressive fracture - Kvasnitsky, M. V.; Kvasnitsky, A. M. (Ukrainian Neurosurgical Journal, 2007)
Surgical stabilization is a standard procedure for distinct types of vertebral fractures without spinal cord damage. We present the observation of case of burst LII vertebra and compressive LIV vertebra fracture that required surgical immobilization of the whole lumbar spine.